Project-Based Learning Design to Enhance Students' Creativity in the Fiqh Element at Junior High School - Farhan, Achmad; Ramadhani, Revina Imelsa; Diana, Alfi Elma; Nasrulloh, Alfian Ahsani (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This research examines the implementation of project-based learning (PjBL) in enhancing students' creativity and active participation at SMP Muhammadiyah 15 Surabaya. Using a qualitative approach with a phenomenological type, this study aims to understand how project-based learning design contributes to the development of students' creativity, especially in the subject of Fiqh. The research subjects consisted of seventh-grade students, who were selected through a purposive sampling technique. The data collection techniques used include observation, in-depth interviews, and documentation. Data analysis was done descriptively by presenting the findings systematically. The results showed that the application of PjBL proved effective in providing space for students to explore Fiqh concepts through real projects relevant to everyday life. This approach not only improves in-depth understanding of the material but also strengthens students' critical thinking skills, collaboration, and creativity in completing tasks. The teacher's role as a facilitator also contributes to increasing students' learning independence, strengthening their involvement in the learning process, and increasing their sense of responsibility for their learning outcomes. Based on these findings, project-based learning can be recommended as an effective method to enhance students' creativity in Fiqh and other subjects that require a practical and contextual approach.